English oral proficiency level required by the main hotels of San Salvador, 2012-2013 - Raimundo Ramos, Francisca Antonia
Since English Language has become one of the most spoken languages worldwide, hotel Industry in El Salvador demands to have personnel with a certain level of English to interact with guests. This becomes a better job opportunity for people who study English as a foreign or second language (EFL; ESL) with the aim of being hired in so prestigious companies. In most of the positions where hotels offer job opportunities, to have some knowledge of English language is a must. To know the different levels of English oral proficiency required for these companies was the main aim of this research. Besides, it was significant to explore other aspects which are relevant when selecting personnel. The methodology hotel Industry uses when evaluating candidates to be integrated into these prestigious companies was investigated aswell.